Analysis of Sharia Business Ethics in a Case Study of Bu Andi's Spicy Cassava Crips MSMEs - Fahlevi, Rizdhan Rizki; Haris, Ibnu (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Islamic business ethics have a positive impact on MSME actors, the principles of Islamic business ethics are monotheism, justice, free will, responsibility, and honesty. Thus, it is necessary to implement production and distribution processes following Islamic business ethics. The purpose of this study is to determine whether MSME actors have implemented business ethics in accordance with Islamic business ethics. In this study, the method used is a descriptive qualitative research method because the researcher wants to describe and write down the conditions seen from the production and distribution processes carried out by MSME actors. The study conducted based on the analysis of Islamic business ethics applied by MSME actors showed that it was not in accordance with the principles of Islamic business ethics that should be.